The Crohn’s Disease Activity Index, Its Derivatives and the Inflammatory Bowel Disease Questionnaire: A Review of Instruments to Assess in Crohn’s Disease - Eric M Yoshida (Canadian Journal of Gastroenterology)
The Crohn’s Disease Activity Index (CDAI) has been used to measure Crohn’s activity for over a quarter of a century. The development of the CDAI is reviewed and its reliability and validity are examined. Instruments used to assess Crohn’s disease that were developed subsequent to the CDAI, including the Harvey-Bradshaw Index, the Cape Town Index and a three-variable version of the CDAI (modified for survey research), are similarly reviewed. The most recent instrument to assess Crohn’s disease, the Inflammatory Bowel Disease Questionnaire, which assesses patients in the domains of bowel, systemic, emotional and social function, is also discussed.